Procuring wrongs - Goudkamp, J (Oxford University Press, 2023)
In certain circumstances, tort law imposes liability for procuring the commission of wrongs. This chapter focuses on one such instance the origin of which is the High Court’s decision in Marex Financial Ltd v Sevillja. In that case, it was held that it was sufficiently arguable for the purposes of securing jurisdiction that it was tortious intentionally and knowingly to induce a violation of rights in a judgment debt. Subsequent cases have confirmed the tort’s existence on the basis that it finds a close analogy with the tort of inducing a breach of contract. This chapter examines the evolution of this new head of liability and its scope. It also explores some of its wider implications for the law of torts.